"Un nodo avviluppato". Rossini's La Cenerentola as a prototype of multimodal resemiotisation. Issue 4 (7th August 2016) - Sindoni, Maria Grazia; Rossi, Fabio
ABSTRACT: Since its early beginnings in Italy in the sixteenth century, opera has always been a multimodal text, integrating verbal, musical, and stage resources. Verbal resources can be unpacked in lyric verse for vocal pieces in closed form, narrative verse or prose for recitative, and stage directions; musical resources include instrumental and vocal music, whereas stage resources incorporate stage design, singers' and dancers' kinesics, and set and costume arrangements. However, opera has been rarely studied in multimodal terms, as it has been mainly explored from musicological standpoints, hence prioritising music and barely taking into account the interplay of other resources. As a case study, epitomising the Golden Age of opera, La Cenerentola by Rossini has been selected, as it exemplifies how the theatrical and compositional conventions of the genre work concurrently with its metatextual components. Stage adaptations will be also analysed in two film operas, that is, Jean-Pierre Ponnelle's La Cenerentola (Germany, 1981) and Carlo Verdone's Cenerentola, Una favola in diretta (Italy, 2014). Opera will be interpreted as a prototype of multi-level resemiotisation, also in a critical light, as the libretto is resemiotised (1) as a musical composition; (2) as a mise-en-scène, and (3) as a film opera.